PENGARUH POINT OF PURCHASE, DISCOUNT DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING KONSUMEN - Hidayati, Annisa; DS, Agus Hermani (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Retail developments are increasing and causing a tight competition among retailers. Tight competition is causing the rise and fall turnover received retailers. This research specifically discusses consumer on Swalayan Mutiara Cahaya Slawi. This report aims to determine the effect of Point of purchase, Discount, and Store Atmosphere on Impulse Buying on consumers Swalayan Mutiara Cahaya Slawi. Type explanatory research, data collection techniques are based interviews questionnaires, sampling technique accidental sampling and purposive sampling with a sample size of 100. The data were analyzed through the validity, reliability, crosstab, coefficient correlation, simple linear regression, multiple linear regression, t test and F, and the coefficient of determination. Quantitative data were analyzed using SPSS 18. The results showed that its categorization impulse buying is high. Then the Point of Purchase categorization is quite interesting, Point of Purchase has a moderate influence on the impulse buying (26.4 percent) as well as the significant and positive impact on impulse buying (0.381). Discount categorization is quite interesting, Discount has a low impact on impulse buying (11.2 percent) as well as the significant and positive impact on impulse buying (0.289). Store Atmosphere categorization was quite comfortable, Store Atmosphere has a strong influence (42.4 percent) as well as the significant and positive impact on impulse buying (0.221). Point of Purchase, Discount and Store Atmosphere has a strong influence on the impulse buying (46.5 percent). In conclusion Point of Purchase, Discount Store Atmosphere and the higher the higher the impulse buying. Swalayan Mutiara Cahaya Slawi is suggested that further improve the product structuring, diversity of discounts products, the frequency of discounts, service and comfort. In addition Swalayan Mutiara Cahaya Slawi in its business of doing business must be accordance with ethics of business. And for consumers to be more careful and wise in shopping activities in order to avoid regret.